Mutagenesis selection and large-scale cultivation of non-green Chlamydomonas reinhardtii for food applications - Cao, Gang; Hu, Kun; Hu, Zhewen; Wu, Qianlong; Liu, Siyuan; Chen, Xiaoping; Meng, Xiangrui; Hu, Zhangfeng; Feng, Li (Frontiers in Nutrition, 2024)
Background: The green alga Chlamydomonas reinhardtii is an accepted food ingredient in the United States of America, the European Union, Singapore, and China. It can be consumed in unlimited quantities. Because this alga is rich in nutrients, protein, rough polysaccharides, and contains a balanced proportion of various amino acids, it is an excellent raw material for food production. While various edible brown and green algae exist on the market, their color and strong grassy flavor have limited their acceptance among consumers, and their application in food additives and animal feed has been limited. Method: Chlorophyll-deficient C. reinhardtii mutants were developed by atmospheric and room temperature plasma technology. Results: A yellow-colored C. reinhardtii variant (A7S80) cultivated in dark conditions was isolated. This light-sensitive variant has a mutation in the chlM gene, and can grow heterotrophically using acetate as a carbon source. Conclusion: Compared to wild type C. reinhardtii, A7S80 has significantly lower chlorophyll levels, a reduced grassy flavor, and more diverse pigments, with considerable potential for commercial application in human and food production, and pharmaceutical and cosmetic industries.